Anomalous Electronic Anisotropy Triggered by Ferroelastic Coupling in Multiferroic Heterostructures. Issue 5 (7th December 2015) - Ju, Changcheng; Yang, Jan‐Chi; Luo, Cheng; Shafer, Padraic; Liu, Heng‐Jui; Huang, Yen‐Lin; Kuo, Ho‐Hung; Xue, Fei; Luo, Chih‐Wei; He, Qing; Yu, Pu; Arenholz, Elke; et al.
Abstract : The ferroelastic strain coupling in multiferroic heterostructures is explored aiming at novel physical effects and fascinating functionality. Ferroelastic domain walls in manganites induced by a stripe BiFeO3 template can modulate the electronic transfer and sufficiently block the magnetic ordering, creating a vast anisotropy. The findings suggest the great importance of ferroelastic strain engineering in material modifications.